2011
DOI: 10.1021/ja2003878
|View full text |Cite
|
Sign up to set email alerts
|

8-Oxoguanosine Switches Modulate the Activity of Alkylated siRNAs by Controlling Steric Effects in the Major versus Minor Grooves

Abstract: Small interfering double-stranded RNAs have been synthesized bearing one or more base modifications at nucleotide positions 4, 11 and/or 16 in the guide strand. The chemically modified base is an N2-alkyl-8-oxo-7,8-dihydroguanine (alkyl = propyl, benzyl) that can alternatively pair in a Watson-Crick sense opposite cytosine (C) or as a Hoogsteen pair opposite adenine (A). Cellular delivery with C opposite led to effective targeting of A-containing but not C-containing mRNA sequences in a dual luciferase assay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…4 In addition, we reported the effect of N 2 -alkylated 8-oxo-7,8-dihydro-2′-deoxyguanosine analogs at specific positions in the guide strand opposite A in the target, a pairing believed to place the N 2 group in the major groove. 23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In addition, we reported the effect of N 2 -alkylated 8-oxo-7,8-dihydro-2′-deoxyguanosine analogs at specific positions in the guide strand opposite A in the target, a pairing believed to place the N 2 group in the major groove. 23 …”
Section: Introductionmentioning
confidence: 99%
“…4 In addition, we reported the effect of N 2 -alkylated 8-oxo-7,8-dihydro-2′-deoxyguanosine analogs at specific positions in the guide strand opposite A in the target, a pairing believed to place the N 2 group in the major groove. 23 However, a systematic study focusing on the effect of solitary major groove modifications at different guide strand positions has not been reported. Furthermore, for this study we chose to modify the purine 7-position because, like the C5 of pyrimidines, this site is located in the major groove of duplex structures and not involved in Watson-Crick base pairing.…”
Section: Introductionmentioning
confidence: 99%
“…In recent work, we showed that N 2 -alkyl-8-oxo-2′-deoxyguanosine analogues (alkyl = propyl, benzyl) ( 23 ), adopting either the syn or anti conformation depending upon their base-pairing partner, can be used as the switchable base to introduce a steric blockade to protein binding in one form (C opposite) vs. the other (A opposite) (see Figure 2). 33,34 …”
Section: Chemical Modification As a Tool To Switch On Sirna Activitymentioning
confidence: 99%
“…28,32,33 Kool and coworkers, and Manoharan, Egli and coworkers reported substitution of pyrimidines (uridine) in the guide strands of siRNAs with more hydrophobic aromatic ring systems (e.g. 2,4-difluorobenzene 29 and 2,4-difluorotoluene 30,36 ), although here silencing efficacy varied depending on the position of the substitution.…”
Section: Introductionmentioning
confidence: 99%